Penatalaksanaan Holistik Penyakit PPOK pada Pasien Lansia Usia 76 Tahun Melalui Pendekatan Kedokteran Keluarga di Puskemas Susunan Baru: Indonesia - Abdillah, Kemas Yahya; Karyus, Aila (Medula, 2024)
Chronic obstructive pulmonary disease (COPD) is a chronic respiratory condition characterized by limited airflow. The Global Burden of Disease Study reports the prevalence of COPD is 251 million cases. One factor that plays a role is long-term smoking behavior, either actively or passively. The clinical manifestation of COPD is a cough with phlegm that persists for more than 3 months, is dry and accompanied by shortness of breath, especially when the patient is active. Management of COPD consists of medical and non-medical. COPD is a lung disease that can be treated and prevented. However, in treating COPD, there needs to be participation and support from the patient and family. This study is a case report. Primary data was obtained through history taking, physical examination and home visits. Secondary data was obtained from patient medical records. Assessment is based on a holistic diagnosis from the beginning, process and end of the study qualitatively and quantitatively. Based on the study. patient Mr. P is 76 years old with a diagnosis of COPD, Mr. P has concerns that the patient's illness could cause him to die. The patient hopes to recover and not take routine medication again. Knowledge about COPD and trigger factors such as trash fumes and cigarette smoke from the surrounding environment are problems that occur in patients. Holistic management is needed for patients with COPD to identify problems that occur in patients so that patients can have a better quality of life.